Racial Unspeakability: Affect and Embodiment in Swiss International Higher Education Institutions - Hernandez, Gian-Louis (Journal of International Students, 2021)
Increasing diversity in international student mobility/migration has gained attention in recent years (Bilecen & Van Mol, 2017). Diversity in international higher education institutions has primarily been understood in terms of diversity of national origin, meaning the dynamics of racial and ethnic differences are not adequately addressed in the literature (Estera & Shahjahan, 2018). This study uses data collected during semi-structured interviews with international and domestic students, as well as administrators, to identify narrations of race, ethnicity, and nationality that delimit a modern/colonial global imaginary (Stein & Andreotti, 2017). It further demonstrates that internal heterogeneity of both sending and receiving countries leads to varied meaning-making schemes for engaging with embodied racial differences and their attendant affective relations (Ahmed, 2013; Wetherell, 2012). The project suggests the term racial unspeakability as a culturally contingent, affective force that governs narrations of race, ethnicity, and nationality.